2016
DOI: 10.1158/0008-5472.can-15-2658
|View full text |Cite
|
Sign up to set email alerts
|

Membrane IL1α Inhibits the Development of Hepatocellular Carcinoma via Promoting T- and NK-cell Activation

Abstract: Hepatocellular carcinoma is a worldwide health problem with limited treatment options and poor prognosis. Inflammation associated with liver injury and hepatocyte regeneration can lead to fibrosis, cirrhosis, and eventually, hepatocellular carcinoma. IL1a is one of the most important inflammatory cytokines involved in inflammation and tumor development. IL1a presents as multiple forms in vivo, including precursor, propiece, membrane, and secreted forms, and their functions have been thought to be different.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 40 publications
1
26
0
3
Order By: Relevance
“…β3GnT8 gene was cloned from peripheral blood mononuclear cells (PBMCs) and then inserted into lentiviral vectors expressing yellow fluorescence protein (YFP) [ 38 ]. The β3GnT8-expressing-lentiviral vectors were packaged into 293T cells and used to transduce SK-Hep-1 and SMMC7721 cells.…”
Section: Methodsmentioning
confidence: 99%
“…β3GnT8 gene was cloned from peripheral blood mononuclear cells (PBMCs) and then inserted into lentiviral vectors expressing yellow fluorescence protein (YFP) [ 38 ]. The β3GnT8-expressing-lentiviral vectors were packaged into 293T cells and used to transduce SK-Hep-1 and SMMC7721 cells.…”
Section: Methodsmentioning
confidence: 99%
“…To assess the effect of RBPJ deficiency on hepatic type 1 ILC function, we chose a model of hepatocellular carcinoma by injection a Hepa1–6 mouse liver cancer cell line. It was shown that cNK and T cells are important in the control of the tumors via IFNg and lytic granules ( 20 ). Three weeks after subcutaneous injection of Hepa1–6 cells, the area of the tumor was significantly increased in RBPJ-deficient mice compared with control mice (Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
“…26 , 27 Studies have suggested that membrane IL1α is immunostimulatory and can promote antitumor immune responses including HCC through activation of T- and natural killer cells. 28 …”
Section: Introductionmentioning
confidence: 99%